Sex and the office : a history of gender, power, and desire - Berebitsky, Julie (Society and the sexes in the modern world., 2012)
In this engaging book--the first to historicize our understanding of sexual harassment in the workplace--Julie Berebitsky explores how Americans' attitudes toward sexuality and gender in the office have changed from the 1860s, when women first took jobs as clerks in the U.S. Treasury office, to the present. Berebitsky recounts the actual experiences of female and male office workers; draws on archival sources ranging from the records of investigators looking for waste in government offices during World War II to the personal papers of Cosmopolitan editor Helen Gurley Brown and Ms. magazine founder Gloria Steinem; and explores how popular sources--including cartoons, advertisements, advice guides, and a wide array of fictional accounts--have represented wanted and unwelcome romantic and sexual advances. By giving sex in the office a history, she provides valuable insights into the nature and meaning of sexual harassment today.